The Integration of Sustainability and ESG Accounting into Corporate Reporting Practices - Dasinapa, Margaretha Beatrik (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: The purpose of this study is to investigate the integration of sustainability and Environmental, Social, and Governance (ESG) accounting into corporate reporting practices. It examines the significance, challenges, and benefits of this integration, focusing on its impact on transparency, accountability, and stakeholder engagement within corporate environments. Research Design and Methodology: The study employs a qualitative literature review methodology involving comprehensive searches of academic databases, journals, and other relevant publications. Predefined criteria guide the selection of literature, and data collection requires reading and critically analyzing scholarly articles, reports, and documents to extract pertinent themes and insights. Findings and Discussion: Key findings from the study underscore the increasing awareness among companies of the importance of sustainability reporting. Despite the benefits, challenges such as issues with data accuracy, comparability, and integration into corporate decision-making processes persist, which can hinder the effectiveness of sustainability reports. Implications: The study suggests that to overcome these challenges, organizations need to adopt integrated reporting frameworks, comply with regulatory requirements, engage more effectively with stakeholders, and leverage technological innovations. These steps will help maximize the value derived from transparent and accountable ESG disclosures, ultimately enhancing company reputation, improving risk management, and boosting stakeholder engagement.